2007
DOI: 10.1039/b705367c
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a fabrication method for a long-term actuated hybrid cell robot

Abstract: We developed a novel method to fabricate a crab-like microrobot that can actuate for a long period in a physiological condition. The microrobot backbone was built with a biocompatible and elastic material-polydimethylsiloxane (PDMS)-by using a specially designed 3D molding aligner, and consisted of three strips of PDMS "legs" connected across a "body." Cardiomyocytes were then plated on the grooved top surface of the backbone, resulting in a high concentration of pulsating cells. These key techniques enabled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 21 publications
0
93
0
2
Order By: Relevance
“…This advantageous property has helped to produce machines that include selfassembling microelectromechanical-system-based cantilevers (15), 2D biohybrid "muscular thin films" (16), and "crab-like" robots (17). These systems were powered by applied electric field stimulation or spontaneous contraction of engineered cardiac muscle, which have also been used as power sources for locomotive machines such as a swimming muscle-elastomer "jellyfish" (18), a self-propelled swimming robot (19), and a walking millimeter-scale "biological bimorph" cantilever (20,21), respectively.…”
mentioning
confidence: 99%
“…This advantageous property has helped to produce machines that include selfassembling microelectromechanical-system-based cantilevers (15), 2D biohybrid "muscular thin films" (16), and "crab-like" robots (17). These systems were powered by applied electric field stimulation or spontaneous contraction of engineered cardiac muscle, which have also been used as power sources for locomotive machines such as a swimming muscle-elastomer "jellyfish" (18), a self-propelled swimming robot (19), and a walking millimeter-scale "biological bimorph" cantilever (20,21), respectively.…”
mentioning
confidence: 99%
“…co-workers utilized a similar approach to engineer a walking biohybrid machine, culturing cardiomyocytes onto grooved PDMS surfaces that allowed for high-density patterning of cells onto the synthetic scaffold or "skeleton." [108] These robots, which continued to walk over a period of 10 d, demonstrated that sustained long-term functionality could be generated using such machines. Kitamori and co-workers have shown that such cardiomyocyte-PDMS composite systems can also be targeted at applications in pumping.…”
Section: Use Of Primary Tissue As Biohybrid Machine Componentsmentioning
confidence: 99%
“…Based on the mathematical model of swimmer tails swinging in liquid actuated by an external magnetism in (5), the applied electric current stimulation led to the tails slapping the liquid with a changing angle between the liquid and tail surface. Combined with the proposed mathematical model of the relationship between the swimmer's swimming velocity and the angle between the liquid and tail in (14), the calculated swimming velocity of the swimmer changes according to various actuation parameters, including the actuation frequency and peak current.…”
Section: Actuation Of the Micro-swimmermentioning
confidence: 99%